Development of Guidance and Counseling Information System Using Vb. 6.0 at SMKN 1 Palibelo - Arjun Mahendra; Fenny Febriyanti; Ahyar Ahyar (STKIP Taman Siswa Bima, 2025)
This study aims to develop and evaluate a desktop-based Guidance and Counseling Information System (GCIS) using Visual Basic 6.0 and MySQL at SMKN 1 Palibelo. The background of the study is the ongoing use of manual methods in managing guidance services, which results in inefficiency and is prone to errors. The research uses the Research and Development (R&D) method with the Waterfall model as a software engineering approach. The system includes features for student data management, counseling case records, and BK activity reporting. The system quality was assessed based on four key indicators: correctness, functionality, maintainability, and usability. Testing results showed zero errors from 2,924 lines of code, fully functional features, maintainable system architecture, and high usability based on user questionnaire responses. These findings indicate that the application of information technology in counseling services improves counselor efficiency, reduces record-keeping errors, and accelerates student data access. The developed system has the potential to be replicated in other schools to support the digital transformation of educational services.